FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR CANDIKUNING BATURITI KABUPATEN TABANAN - I WAYAN MULA SARJANA (Universitas Mahasaraswati Mataram, 2021)
This study aims to determine the effect simultaneously or partially of venture capital (X1), working hours (X2), and length of business (X3), on the income of traders in Candikuning Market, Baturiti, Tabanan Regency (Y). Primary data is taken by questionnaire from a sample of 47 traders at Candikuning Market. Samples are taken using probability sampling techniques from various blocks. Data are analyzed using multiple linear regression. The results showed that working capital, working hours, and length of business simultaneously had a significant effect on the income of traders in Candikuning Market, Baturiti, Tabanan Regency. Working capital and working hours partially have a positive and significant effect on the income of traders in the Candikuning Baturiti Market, Tabanan Regency. Meanwhile, the length of business does not affect the income of traders in Candikuning Market, Baturiti, Tabanan Regency